Broad ligament ectopic pregnancy: a dilemma to diagnose - Mittal, Shweta; Gupta, Vinita; Chawla, Dolly; Pundir, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Broad ligament ectopic pregnancy is a rare and serious form of extrauterine pregnancy with a high risk of maternal mortality. There are no specific clinical features. Ultrasonography may help in diagnosis but definitive diagnosis is made only during surgery. A 20-year-old woman with previous 2 abortions presented with acute abdomen. She had no history of amenorrhoea but there was history of two episodes of bleeding in the last month at an interval of 14 days, each episode lasting for two-three days. The last episode of bleeding was 10 days back. Her urine pregnancy test was done and it was positive. There was marked abdominal tenderness with guarding and rigidity. Per vaginal examination revealed marked tenderness in the right fornix and cervical motion tenderness, uterus size could not be assessed due to tenderness. It was diagnosed as a case of ruptured ectopic pregnancy. Since she was haemodynamically unstable, emergency laparotomy was done. She had a right sided broad ligament ectopic pregnancy which had ruptured. The tissue was completely removed and haemostatic sutures were taken. High index of clinical suspicion, early diagnosis and prompt surgery is the key to management.